ANALISIS KINERJA PERUSAHAAN DENGAN METODE BALANCED SCORECARD PADA KUSUMA SAHID PRINCE HOTEL SURAKARTA - Styaningrum, Farida; Riani, Asri Laksmi (Jurnal Pendidikan Insan Mandiri, 2015)
Kusuma Sahid Prince Hotel (KSPH) is one of the hotels in Surakarta. The performance measurement at KSPH Surakarta all this time is only viewed from financial aspect. The financially measurement of performance is not enough to reflect the actual company performance, so it is needed the more comprehensive method of performance measurement as a benchmark of target attainment of the company. Balanced Scorecard is an alternative choice for the measurement of a company performance. The objective of the research is to gain result about the application of Balanced Scorecard in measuring performance at KSPH Surakarta in the year of 2011-2013 through four perspectives; financial, customer, internal business process, also learning and development perspective. This research used qualitative approach with descriptive method type job and activity analysis. Data analysis technique used in this research was interactive model. The result of this research shows that performance at KSPH Surakarta in the year of 2011-2013 based on the analysis result toward the four perspectives of Balances Scorecard achieves at 64,583%, it means that KSPH Surakarta has the good performance quality in achieving target strategy for every perspective in Balanced Scorecard. Keywords: performance measurement, Balanced Scorecard, Kusuma Sahid Prince Hotel (KSPH) Surakarta